Determinants of financial inclusion in Sub-Saharan Africa countries: Does institutional infrastructure matter? - Kazeem B. Ajide (CBN Journal of Applied Statistics, 2017)
The paper examines the determinants of financial inclusion by specially accounting for the role of institutions in a panel of eighteen (18) sub-Saharan Africa (SSA) countries using a dynamic system of Generalized Method of Moments (SYS-GMM). The emanated findings consistently stress the importance of institutions together with other control variables like GDP per capita, inflation, bank concentration and z-score as key drivers of FI. In the final analysis, the paper emphasizes the importance of using dimension by dimension indicators of governance as well as a composite governance index instead of relying solely on the latter as a basis of informing policy decisions as both yield different policy outcomes.
Keywords: C23; O12; G23; G38; 330; Dynamic Panel Systems; Financial Inclusion; Generalized Method of Moments (GMM) and Institutions